A Histopathological Study of Skin Lesions in Individuals with Oculocutaneous Albinism in Togo in 2019. (29th July 2020) - Saka, Bayaki; Teclessou, Julienne Noude; Akakpo, Sefako Abla; Gnossike, Piham; Doh, Kwamé; Adam, Saliou; Mouhari-Toure, Abas; Mahamadou, Garba; Kassang, Panawé; Elegbede Moise, Yvette; Darre, Tchin; Kombate, Koussake; et al.
Abstract : Objective . The aim of this study was to study the histopathological patterns of skin lesions in persons with albinism (PWA) in Togo in 2019. Method . During two mobile skin care clinics in 2019, biopsies/excisional biopsies were performed in PWA in case of clinical doubt or in front of lesions suspected to be cancerous for histological examination. Anatomopathological reports were thus analysed. Results . During the two mobile skin care clinics, 115 biopsies/excisional biopsies were carried out in 79 PWA, with a mean age of 24 ± 16.1 years. Histological examination led to a diagnosis in 110 cases (95.6%) and was inconclusive in 5 cases (4 cases of uncertain histological diagnosis and one case of nonspecific histological lesions). Fourteen different histological diagnoses were made, with a frequency ranging from 0.9% (one case) to 26.9% (31 cases). The four most frequent diagnoses in descending order were basal cell carcinomas (BCCs) (31 cases; 26.9%), invasive squamous cell carcinomas (SCCs) or Bowen's disease (23 cases; 20%), keratosis (20 cases; 17.3%), and cysts (seven cases; 6.1%). The 54 skin carcinomas were diagnosed in 33 (41.8%) of the 79 patients who underwent skin biopsies/excisional biopsies. The BCC/SCC ratio was 1.3. No cases of cutaneous melanoma had been diagnosed. Conclusion . Skin cancers represent the main histological diagnosis in PWA (46.9%) in Togo in 2019. The pattern of cutaneous malignancies in PWA shows the same trend as that seen in Caucasians with a predominance of basal cell carcinomas.